Introduction to the history of Christianity - Dowley, Tim, ed.; Briggs, John H.Y. , ed.; Linder, Robert D., ed.; Wright, David F., ed. (Minneapolis : Fortress Press, 2018)
Now in its third edition, Tim Dowley's masterful one-volume survey of church history has an updated design and new content, particularly in the section covering most recent Christian history. The inviting full-color format includes many new images and updated maps, while maintaining many of the features that made the second edition a popular volume for the classroom. Dowley has assembled a global cast of respected scholars to write the full story of the rise of the Christian faith and to provide a rounded picture of the worldwide development of Christianity. The volume has been praised as accurate, scholarly, and balanced. Its writers are committed to Christianity but also to the unhindered pursuit of truth that does not avoid the darker aspects of the varied story of Christianity. The accessible text is supported by detailed timelines, maps, profiles of key figures in Christianity, colorful images, and a complete glossary. Each section includes questions for discussion.
43. Present and future: the church in an ever-changing world.
Includes index.
Keywords: Church history; Church history -- Chronology -- Charts, diagrams, etc